2020
DOI: 10.3390/diagnostics10080520
|View full text |Cite
|
Sign up to set email alerts
|

AZGP1 Protein Expression in Hormone-Naïve Advanced Prostate Cancer Treated with Primary Androgen Deprivation Therapy

Abstract: Biomarkers for predicting the risk of castration-resistant prostate cancer (CRPC) in men treated with primary androgen deprivation therapy (ADT) are lacking. We investigated whether Zinc-alpha 2 glycoprotein (AZGP1) expression in the diagnostic biopsies of men with hormone-naïve prostate cancer (PCa) undergoing primary ADT was predictive of the development of CRPC and PCa-specific mortality. The study included 191 patients who commenced ADT from 2000 to 2011. The AZGP1 expression was evaluated using immunohist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“…A similar result was obtained from a Chip-Seq study that AZGP1 acted as an androgen-responsive gene to mediate proliferation and metastasis of prostate cancer cell via the contribution of androgen receptor [ 63 ]. In addition, a clinical study included 191 patients who underwent androgen deprivation therapy showed that low AZGP1 expression was associated with a shorter survival time in prostate cancer patients [ 64 ]. Also, the low expression of AZGP1 could be used to predict the recurrence of margin-positive, localized prostate cancer [ 65 ].…”
Section: Discussionmentioning
confidence: 99%
“…A similar result was obtained from a Chip-Seq study that AZGP1 acted as an androgen-responsive gene to mediate proliferation and metastasis of prostate cancer cell via the contribution of androgen receptor [ 63 ]. In addition, a clinical study included 191 patients who underwent androgen deprivation therapy showed that low AZGP1 expression was associated with a shorter survival time in prostate cancer patients [ 64 ]. Also, the low expression of AZGP1 could be used to predict the recurrence of margin-positive, localized prostate cancer [ 65 ].…”
Section: Discussionmentioning
confidence: 99%